Copper and Magnesium Deficiency are Associated with Osteoporosis in Southern Gaza Patients - Mahmoud I. Elhabiby; Ayman M. Abu Mustafa; Abdelmarouf H. Mohieldein; Esraa M. Elnabaheen (European Scientific Journal, ESJ, 2020)
Osteoporosis is a common disease in old ages, trace minerals are central components of bone density and hardness. The present study aims to measure copper, magnesium, iron, calcium and phosphorus levels in osteoporotic southern Gaza patients and control groups. A case –control study included 35 osteoporotic patients and 35 controls aged 40-70 years. Copper, magnesium iron, calcium and phosphorus levels were measured in the serum at PalestinianMedical Relieve Society-Gaza by absorption spectrophotometry method-XLFS Kit (Diasys Diagnostic System GmbH). Serum copper and magnesium levels in osteoporotic patients (74.3±9.8μg/dL 1.56±0.18mg/dl) respectively is significantly (p<0.001) lower than control (98.3±15.2μg/dL, 2.06±0.13mg/dl ). The present work indicated a positive correlation between copper and magnesium levels (r=0.627, p<0.00), positive correlation between copper and number of daily meals (r=0.263, p<0.030), and also positive correlation between calcium and daily exercises (r=0.449, p<0.010). In conclusion copper and magnesium levels are significantly lower in postmenopausal women and men with osteoporosis. Optimizing levels of those trace minerals in old people is beneficial in prevention of osteoporosis. Daily exercises and ingestion of food containing trace minerals is highly recommended for this age group.